Gastrointestinal symptoms among recreational long distance runners in China: prevalence, severity, and contributing factors - Zhao, Xueyuan; Chen, Yan; Li, Xiangxin; Wen, Wei; Zhang, Jingyi; Qiu, Junqiang (Frontiers in Nutrition, 2025)
PurposeGastrointestinal (GI) symptoms are prevalent among endurance athletes, especially marathon runners, and can negatively affect performance and wellbeing. However, data on the prevalence and nutritional contributors to GI symptoms in Chinese recreational long distance runners remain limited. This study aimed to investigate the prevalence, severity, and dietary influences of GI symptoms in this population.MethodologyA total of 805 valid responses were collected through an online and offline questionnaire conducted in China between January and December 2024. Participants were recreational long distance runners recruited via running clubs, community organizations, sports associations, and online platforms. The questionnaire covered six areas: demographics, exercise habits, dietary strategies, GI symptom severity and frequency, influencing factors, and knowledge and attitudes. GI symptoms during races were assessed using the Gastrointestinal Symptom Rating Scale (GSRS), which includes 11 symptoms rated on a 7-point Likert scale.ResultsNotably, 26.1% of participants reported GI symptoms during races, with bloating (18.6%), urge to defecate (17.8%), and stomach pain (16.5%) being the most frequent. Symptoms peaked in prevalence and severity during the middle phase of the race. GI symptoms were more common in males (27.9%) than females (20.8%), and runners aged 34 years and younger had a higher symptom rates. Nutritional factors, particularly pre- and mid-race dietary strategies, significantly influenced symptom occurrence. Foods high in fat, protein, fiber, or fermentable carbohydrates were commonly associated with GI distress. Eating within 30 min before a race increased the risk of bloating and urge to defecate. The use of energy gels, sports drinks, and hydration strategies also correlated with higher GI symptom risk. Other contributing factors included a history of GI issues and high monthly running volume.DiscussionThe findings underscore the importance of individualized dietary planning to reduce GI symptoms among recreational long distance runners. Adjusting pre-race meal timing and avoiding certain food types may mitigate discomfort. In addition to nutrition, variables such as sex, age, training load, and medical history should be considered in preventive strategies. Future research should explore tailored nutrition and training approaches to improve athlete health and performance during endurance events.